2014
DOI: 10.1155/2014/950516
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gene and Protein Expressions in Rats Residing in Standard Cages with Those Having Access to an Exercise Wheel

Abstract: Lifelong physical inactivity is associated with morbidity in adulthood, possibly influenced by changes in gene and protein expressions occurring earlier in life. mRNA (Affymetrix gene array) and proteomic (2D-DIGE MALDI-TOF/MS) analyses were determined in cardiac tissue of young (3 months) and old (16 months) Sprague-Dawley rats housed with no access to physical activity (SED) versus an exercise wheel (EX). Unfavorable phenotypes for body weight, dyslipidemia, and tumorogenesis appeared more often in adult SED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…A study has previously shown that low activity of Gpx1 is an independent risk factor of cardiovascular events [ 60 ]. The increase in Gpx1 with exercise is also coherent with the literature [ 61 , 62 ] and concords with the known antioxidant properties of chronic exercise [ 16 , 17 ]. Therefore, our data, in support of the current knowledge, suggest that overexpression of Gpx1 is one of the mechanisms responsible for the antioxidant protection by exercise.…”
Section: Discussionsupporting
confidence: 88%
“…A study has previously shown that low activity of Gpx1 is an independent risk factor of cardiovascular events [ 60 ]. The increase in Gpx1 with exercise is also coherent with the literature [ 61 , 62 ] and concords with the known antioxidant properties of chronic exercise [ 16 , 17 ]. Therefore, our data, in support of the current knowledge, suggest that overexpression of Gpx1 is one of the mechanisms responsible for the antioxidant protection by exercise.…”
Section: Discussionsupporting
confidence: 88%
“…Cardiac gene expression changes due to exercise training in young rats have been well-studied. These studies showed that mitochondrial or metabolic gene expression in the young rat heart to either increase (Hall et al, 1994 ; Rimbaud et al, 2009 ; Dobrzyn et al, 2013 ; Wadley et al, 2016 ) or not change (Murakami et al, 1995 ; Iemitsu et al, 2003 ; Alessio et al, 2014 ) with exercise training compared to young sedentary rats. Specifically, young hearts respond to exercise training by increasing the expression of genes associated with glucose transport (Hall et al, 1994 ; Rimbaud et al, 2009 ), fatty acid oxidation (Rimbaud et al, 2009 ; Dobrzyn et al, 2013 ), and mitochondrial biogenesis (i.e., PGC-1α and Cox4il; Rinaldi et al, 2013 ; Wadley et al, 2016 ).…”
Section: Limitationsmentioning
confidence: 99%
“…We have to concur with Santos et al (2014) that there is a clear necessity to continue efforts to unravel the effects of the various physical activity traits on the expression of genetic variance in body composition. Alessio et al (2014) used a rat model to test whether exercise modulates the normal aging of the heart muscle. They compare the whole genome gene expression profile as well as cardiac proteomics signature of rats aged 3 months and 16 months.…”
Section: Effects Of Exercise That May Be Modulated By Genotypementioning
confidence: 99%
“…Alessio et al (2014) used a rat model to test whether exercise modulates the normal aging of the heart muscle. They compare the whole genome gene expression profile as well as cardiac proteomics signature of rats aged 3 months and 16 months.…”
Section: Effects Of Exercise That May Be Modulated By Genotypementioning
confidence: 99%